Pengaruh Kebijakan Aturan Pemerintah Selama Covid-19 Yang Dapat Diterapkan Hingga Saat Ini (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The COVID-19 pandemic has presented multidimensional challenges for Indonesia, requiring holistic government policies to maintain public health and restore the economy. This journal aims to formulate effective and sustainable government regulatory policies since the pandemic until the present. On the economic recovery side, this policy includes direct financial assistance to workers and MSMEs, as well as ease of financing to encourage economic growth. Increasing investment is a key strategy with the formation of an investment coordination team. Regular monitoring and evaluation will be implemented through a real-time reporting system to ensure policy effectiveness. This research uses quantitative methods with a cross sectional design. The sampling technique in this research is incidental sampling. It is hoped that this journal can become a basis for the government and related stakeholders in formulating policies that are adaptive and responsive to changing pandemic conditions. With joint support, it is hoped that Indonesia can move towards a sustainable and resilient recovery through measurable and well-planned policies.